Coral Reef Health Index On Sangiang Island - Rahma Aprilian; Dietriech Geoffrey Bengen; Erlania Erlania; Ofri Johan; Idris Idris (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2021)
The coral reef is massive deposits of calcium carbonate produced from coral animals that are symbiotic with zooxanthellae. One of the activities carried out as an effort to improve the sustainability of coral reefs is monitoring the health condition of coral reefs. The coral reef health index value is based on benthic components and fish components. The benthic component consists of variable life coral cover and the level of coral reef resilience determined based on macroalgae, rubble, and life coral. Fish component is the total biomass of target reef fish. The highest coral reef health index value is at value 10 and the lowest value is at value 1. This study aimed to determine the value of the health index on Sangiang Island. This research was conducted on 16-18 February 2019 on Sangiang Island on three dive stations are Legon Bajo, Legon Waru, and Tembuyung. Data collection of benthic components uses the Underwater Photo Transect (UPT) method and data collection of fish components uses the Underwater Visual Census (UVC) method. The results showed that the coral reef health index on Sangiang Island was at values 6 and 5, means the live coral cover on Sangiang Island was included in the high and medium category, and the level of coral reef resilience or recovery potential was included in the high category, while the total biomass of the target reef fish is still in the low category, only a few species of fish were found that belong to the target reef fish.